Sulphated AlMCM-41: Mesoporous solid Brønsted acid catalyst for dibenzoylation of biphenyl - Poh, Ng Eng; Nur, Hadi; Muhid, Mohd Nazlan Mohd; Hamdan, Halimaton (Elsevier, 2006)

(untitled)
Sulphated mesoporous solid Brønsted acid catalyst (SO4-AlMCM-41) was prepared by impregnation of sulphuric acid on the surface of H-AlMCM-41. Characterization of SO4-AlMCM-41 by pyridine adsorption studies and 27Al MAS NMR showed that the presence of Brønsted acidity was correlated with octahedrally coordinated aluminium and solvent environment. Catalytic study demonstrated that the SO4-AlMCM-41 catalyst has a higher activity in the dibenzoylation of biphenyl with benzoyl chloride than sulphuric acid, H-AlMCM-41 and sulphated amorphous silica.